A School-Based Project: Increasing Ontario Pre-Service Teacher Candidates' Experiences With Cultural Diversity - Frank Brathwaite; Brad Porfilio (Networks: An Online Journal for Teacher Research, 2004)
This paper details a service-learning project involving thirty-two Ontario, White pre-service teachers in Buffalo, New York. We provided reflective activities to help future teachers develop an awareness and understanding of how unjust educational practices inhibit the educational performance of marginalized students. Although fourteen students did increase their awareness of urban school conditions and communities, we also learned that neither our teaching nor the service-project pushed eighteen participants to 'see' how educational practices work to perpetuate the racial and social class structure. Armed with this knowledge, we recognized that more time and energy must be expended to create research activities as well as authentic learning experiences to guide prospective teachers to recognize institutional practices that create social inequalities.